Evaluation of disease management approaches for powdery mildew on Cannabis sativa L. (marijuana) plants. Issue 3 (4th May 2021) - Scott, Cameron; Punja, Zamir K.
Abstract: Powdery mildew on cannabis ( Cannabis sativa L., marijuana), caused by Golovinomyces cichoracearum, reduces plant growth and overall quality. To investigate disease management options, biological, chemical and physical approaches were assessed. A mildew-susceptible strain, 'Copenhagen Kush', was grown indoors with continual exposure to mildew inoculum. Treatments were applied weekly over a four-week period to groups of four plants once mildew infection had established itself. Trials were repeated thrice under varying initial disease pressures. Disease assessments were made weekly and the percentage of area infected on 30 leaflets per plant was used to calculate a disease rating score for treated and control plants. Disease progress curves were plotted and AUDPC values were determined for each treatment. To test the effect of UV-C light on mildew development, plants were exposed daily for 3–5 s over 28 days to UV-C light. The response of 12 cannabis strains to powdery mildew infection was assessed after exposing them to inoculum over a period of two weeks. The most effective treatments that significantly ( P < 0.05) reduced disease in three trials were Luna Privilege SC (fluopyram), Regalia ® Maxx, MilStop ®, Rhapsody ASO TM, neem oil, and Stargus ® . Treatments that were less effective included ZeroTol ®, boric acid, and Actinovate ® SP. Daily exposure of plants to UV-C light significantly reduced disease (by 45.2%, P < 0.05). Seven of 12 cannabis strains had significantly lower disease severity compared with the other five strains. The disease management strategies evaluated in this study have potential for reducing powdery mildew development on cannabis.